Heart Rate Variability in Dental Science - Drury, Robert L.; Simonetti, Scott A. (Frontiers in Medicine, 2019)
Dentistry has made progress as a profession by integration with both medicine and other human sciences, especially when it uses empirical metrics to study process and outcome variables. Notably, progress in our understanding of genomic, biomic and other molecular biological phenomena has been valuable. As has been identified by Drury (1,2), it is proposed in this commentary that the inclusion of heart rate variability (HRV) as a biomarker of health may further this integrative progress. The small literature of dental use of HRV will be selectively reviewed and relevant exemplars for other important health applications of HRV will be discussed. This will lead to a proposed agenda for researching HRV’s value to professional dentistry as a human health and wellness profession